PENGARUH MEDIA SOSIAL INSTAGRAM DAN DAYA BELI MASYARAKAT TERHADAP MINAT BERKUNJUNG DI KEDAI YOI SIDOARJO - Afifuddin, Luthfi; Cahya, Septyan Budy; Rakhmawati, Dwi Yuli (Program Studi Pendidikan Tata Niaga Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2023)
Social media to have a big impact in the modern era especially since increased the globalization.Having an aspect which is of significant to all line included in the centre of the economy with marketing focus to segmentation.This study using the purchasing power, social media, visit the interest or Visiting Intention with the approach to understand the influence of social media instagram customers to interest and a visit in a tavern yoi sidoarjo which after triangulation lab data and processes interpretation has done will produce the variables of social media instagram and the people purchasing power has the effect on interest visit tavern yoi sidoarjo. Keyword: Social Media, Purchasing Power, Visiting Intention